Spatial dispersal of Aedes albopictus mosquitoes captured by the modified sticky ovitrap in Selangor, Malaysia - Muhammad Aidil, Roslan; Romano, Ngui; Muhammad Fathi, Marzuki; Indra, Vythilingam; Aziz, Shafie; Sabri, Musa; Wan Yusoff, Wan Sulaiman (PAGEPress®, Pavia, Italy., 2022)
Dengue is a major mosquito-borne disease in many tropical and sub-tropical countries worldwide, with entomological surveillance and control activities as the key management approaches. This study aimed to explore the spatial dispersal of the vector Aedes albopictus, captured by the modified sticky ovitrap (MSO) in residential areas with low-rise buildings in Selangor, Malaysia. Distribution maps were created and shown as temporally distinguished classes based on hotspot analysis by Getis-Ord; spatial autocorrelation assessed by semivariograms using the exponential Kernel function; and universal Kriging showing areas with estimated high and low vector densities. Distribution, hotspot and interpolated maps were analysed based on the total number of mosquitoes by month and week. All maps in the present study were generated and visualised in ArcMap. Spatial autocorrelation of Ae. albopictus based on the monthly occurrence of Ae. albopictus was found in March, April, October, November and December 2018, and when based on the weekly numbers, in weeks 1, 2, 3, 5, 7, 12, 14, 25, 26, 27, 31, 33, 42, 49 and 52. Semivariograms, based on the monthly and weekly numbers of Ae. albopictus, indicated spatial autocorrelation of the species extending between 50 and 70 m. The mosquito density maps reported in this study may provide beneficial information to facilitate implementation of more efficient entomological control activities.